Graphite platelet films deposited by spray technique on low density polyethylene substrates. (2020) - Di Bartolomeo, Antonio; Iemmo, Laura; Urban, Francesca; Palomba, Mariano; Carotenuto, Gianfranco; Longo, Angela; Sorrentino, Andrea; Giubileo, Filippo; Barucca, Gianni; Rovere, Massimo; Tagliaferro, Alberto; Ambrosone, Giuseppina; et al.
Highlights: Large area thin films can be produced by spraying Graphit 33 lacquer on LDPE. Thin films are composed of graphite platelets (GP) electrically connected. The graphite platelets are aligned parallel to the interfacial plane. The resistance of the GP films on LDPE increases as a function of temperature. Thermoresistive properties of GP films on LDPE are useful for plastic electronics. Abstract: An inexpensive technique based on spraying a graphite lacquer on low-density polyethylene (LDPE) substrate has been proposed to produce large area thermoresistive films. Scanning electron microscopy analysis shows that the coatings are composed of overlapped graphite platelets. Raman measurements reveal that the deposited films are made of a good quality graphitic material. Electrical measurements as a function of temperature of graphite platelet films on LDPE have been carried out between −40 and +40 °C and it has been found that the resistance of the films increases with increasing the temperature. This behaviour, opposite to that of graphite material, could be attributed to the thermal expansion effects of the substrate. Graphite platelet films deposited on LDPE are promising materials for thermoresistive applications in plastic electronics.